NAVIGATING INTIMACY IN A MOBILE WORLD: ROMANTIC RELATIONSHIPS IN THE DIGITAL NOMAD LIFESTYLE - Miguel, Cristina; Lutz, Christoph; Xiao, Yunhao; Majetić, Filip; Perez-Vega, Rodrigo (AoIR Selected Papers of Internet Research, 2026)
The rise of digital nomadism, where individuals combine remote work with travel, offers new opportunities for personal freedom and cross-cultural experiences, yet also presents challenges in maintaining romantic relationships. This study examines how digital nomads (DNs) navigate the complexities of romantic relationships while adhering to a nomadic lifestyle. Through participant observation, 20 in-depth interviews with DNs, and an analysis of the r/digitalnomad sub-reddit, this paper explores: 1) how DNs explain their experience with romantic relationships in relation to their lifestyle; 2) how they deal with the difficulties of forming and maintaining romantic relationships. Guided by relational work and inter-role conflict theories, we identify four conflict types within DNs’ romantic relationships: attitude-based (e.g., prioritizing the lifestyle over relationships), location-based (e.g., travel plans that conflict with the formation of stable romantic relations), time-based (e.g., time allocation choices), and money-based (e.g., not having sufficient financial resources to maintain a transient lifestyle). To address these conflicts, our interviewees used resource conservation, segmentation, and compensation mechanisms. The study highlights the prioritization of lifestyle over relationship stability and the critical role of boundary management in sustaining intimate bonds. Moreover, it identifies strategies DNs use to find partners within their lifestyle, including attending DN events organised via social media and using dating apps, though these practices come with their own challenges, particularly in navigating varying cultural norms. The paper contributes to our understanding of intimacy in the context of digital nomadism, offering insights into the evolving dynamics of romantic relationships in an increasingly mobile and digital world.